Analisis Sentra Komoditas Unggulan Sektor Pertanian di Kabupaten Tanah Datar - Rahmadini; Maizul Rahmizal (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the flagship commodities and production centers for each flagship commodity in the agricultural sector of Tanah Datar Regency. This study uses secondary data from the Central Statistics Agency (BPS) and the Tanah Datar Regency Agriculture Office for the 2021–2025 period, covering 14 subdistricts, with data on total production (tons) in the food crops, vegetable horticulture, fruit horticulture, bio-pharmaceutical horticulture, and plantation crops subsectors. The analytical methods used include the Static Location Quotient (SLQ), Dynamic Location Quotient (DLQ), and a combination of SLQ and DLQ. The results of the study indicate that the flagship commodities in Tanah Datar Regency include: rice, sweet potatoes, peanuts, curly chili peppers, tomatoes, chayote, cardamom, noni, avocados, and cloves. Each commodity has production centers spread across specific subdistricts, reflecting regional differences in potential and comparative advantages. This distribution pattern indicates that each subdistrict plays a distinct role in supporting agricultural sector development, thereby serving as a foundation for formulating region-based policies for the development of key commodities.